Fire Model Test on Temperature Field in the Rescue Station of an Extralong Railway Tunnel - Yanhua Zeng; Kelin Liu; Yong Fang; Xianfu Zhang; Yun Bai (Advances in Civil Engineering)
A rescue station is necessary for an extralong railway tunnel, whose length is generally greater than 20 km. In the rescue station, passenger evacuation, fire fighting, and protection of passengers are organized. It is important to discover the temperature distribution in a rescue station where a train is on fire. This paper performs a similarity simulation model test at 1 : 10 geometric scale to investigate the temperature field in a rescue station. A gasoline pool fire was used as the fire source. The influences of the fire source position and ventilation condition on the temperature field were studied. The results show that (a) the temperature distribution along the tunnel is stable without ventilation, the temperature is lowest when the fire occurs 50 m from the entrance; (b) the fresh air stirred up by fans promotes burning and increases the temperature; (c) the chimney effect causes the temperature field to skew in an uphill direction; (d) the opening of both fans in the adit makes the high-temperature zone to connect through; and (e) the temperature increase at the rescue station can be divided into four stages, and the response of different fire source positions to the opening of fans is not consistent. These findings provide a basis for personnel escape design and a foundation for further study of temperature distribution in a tunnel with a rescue station.